A new strategy for measuring tourism demand features - Asensi Descals-Tormo; María-José Murgui-García; José-Ramón Ruiz-Tamarit (National Accounting Review)
Understanding tourist behavior, demand elasticities, and the purchasing power of regular tourists visiting a destination is of great interest to the tourism industry for business strategy and to governments for tourism public policy. Here, we propose a new method to empirically estimate the own-price and cross-price elasticities of demand for tourist goods and services, as well as an innovative way to measure the average tourist's marginal utility of income. In the tourism sector, we consider that there are two relevant markets: one for tourist goods and services and the other for accommodation. These are separate but interrelated because of the feedback between demands for lodging and tourism products through a vertical relationship of complementarity. The optimal solution to the tourist choice problem consists of a primary demand for tourist services and a derived demand for overnight stays. We focus on obtaining robust estimates of the elasticities corresponding to the former by forecasting the latter. Most of the empirical modeling of tourism demand consists of ad hoc equations that are not directly attached to a specific theoretical framework. Our paper provides a solid characterization of the empirical linkages between the demands for tourist goods and services and accommodation using economic theory. This paper extends existing theory and makes an important contribution to the empirics of tourism economics, with an application to the tourism database of Australia, Canada, Spain, and the United States that quantifies demand elasticities and identifies the socioeconomic status of their respective tourists.